2013
DOI: 10.1177/0960327113515502
|View full text |Cite
|
Sign up to set email alerts
|

Getting stung by black scorpion Androctonus crassicauda

Abstract: Importance of the correct diagnosis in the correct early management of a scorpion stung patient by using antivenom is not emphasized, particularly when there are little evidences. A 65-year-old female was brought to our emergency department with the chief compliant of being stung by an unknown object 3 h earlier while traveling in an intercity bus. She became agitated and simultaneously experienced tachycardia, very severe generalized sweating, cold and wet extremities, bilateral diffuse crackle in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Androctonus crassicauda is called the black scorpion, known as a non-digging species with a size up to 12 cm in length. The results of previous studies indicated 28% of scorpionism cases belonged to this scorpion in the west of Iran ( 31 , 32 ). Severe pain in patients and more deaths in infants due to its sting have been observed ( 33 ).…”
Section: Discussionmentioning
confidence: 96%
“…Androctonus crassicauda is called the black scorpion, known as a non-digging species with a size up to 12 cm in length. The results of previous studies indicated 28% of scorpionism cases belonged to this scorpion in the west of Iran ( 31 , 32 ). Severe pain in patients and more deaths in infants due to its sting have been observed ( 33 ).…”
Section: Discussionmentioning
confidence: 96%
“…crassicauda, as another venomous species, has been reported from Egypt, Jordan, Syria, Turkey, Iraq, Saudi Arabia, and Azerbaijan (Karataş and Ç olak, 2015) and was also collected in our study. It is called the black scorpion, known as a non-digging species (Aghabiklooei et al, 2013;Vazirianzadeh and Salahshoor, 2015). After its sting, patients documented severe pain and it was registered high number of infant deaths (Khodadadi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are various physiopathological and pharmacological studies about the species of A. australis, A. crassicauda and A. amoreuxi (e.g. Saidi et al, 2013;Aghabiklooei et al, 2013;Fetaih et al, 2013). However, no information is available about the black fat-tailed scorpion or A. bicolor.…”
Section: Introductionmentioning
confidence: 99%